The Lyric Essay as an Aesthetic-Hermeneutical Experience - Hernández Carmona, Luis Javier (2017)
A theorization is proposed for the lyric essay and the generation of the aesthetic-hermeneutic experience from the application of ontosemiotics as a methodological perspective. A discussion is presented of discursive-literary practices containing meta-reflection which, from extratextuality, responds to metaphorized approaches that for the autonomy of the text and the splits of the enunciating subject require analytical strategies focusing on the referential quadrant author-text-reader-context. Theories on the essay are reviewed, including those of Montaigne, Lukács, Adorno and Nicol, to propose the essay as a balance between the objective and transcendental subjectivity.